(untitled) (Scientific journal of the Fergana State University, 2026)
The article analyzes the historical and philosophical roots of the phenomenon of alienation, the characteristics of the manifestation of individual alienation in society, the role of intellectual values in the struggle against human alienation, the forces exploiting human alienation in the era of global development, and the strategic importance of the national idea in preventing human alienation in Uzbekistan.